Gender typicality of occupational aspirations among immigrant and native youth: the role of gender ideology, educational aspirations, and work values - Gambaro, Ludovica [Verfasser]; Wilhelm, Janna [Verfasser]; Schober, Pia Sophia [Verfasser] (My University, 2023)
„The gender typicality of adolescents' occupational aspirations helps sustain occupational segregation, ultimately contributing to maintain gender stratification. According to sociological and psychological perspectives, adolescents develop occupational aspirations by drawing on their gender beliefs and work-related values. Yet few empirical studies have examined the contribution of these value orientations specifically to the gender typicality of occupational aspirations. Moreover, although children from immigrant backgrounds make up an ever-increasing share of school-age students, there is scant evidence on the gender typicality of their occupational aspirations relative to those of their majority peers. This study investigates variations in the gender typicality of occupational aspirations among adolescents from immigrant and non-immigrant backgrounds at around age 16. It also explores how the gender typicality of different groups' aspired occupations relates to differences in gender ideologies, in educational aspirations, and in the importance attributed to three work values: the possibility to earn high income, to help others, and to think and solve problems. Drawing on a harmonized survey from England, Germany, the Netherlands and Sweden, the analysis uses a sample of 8,574 adolescents, including 1,510 girls and 1,336 boys from immigrant backgrounds. Multinomial logistic regressions estimated the associations with aspired occupations, classified as masculine, integrated, feminine or ultrafeminine based on the proportion of women working in them. Results indicate that boys and girls of immigrant origin aspired to somewhat less gender-typical occupations than their majority peers. Among girls, these differences would be even larger if they were not suppressed by the more traditional gender ideologies held by girls from immigrant backgrounds. In terms of mediating mechanisms, our findings suggest that more ambitious educational aspirations may partly explain these differences. These findings indicate that distinguishing between multiple dimensions of adolescents' work-related values hint at different underlying mechanisms in the formation of adolescents' occupational aspirations.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 1.5 Migranten; G 2.4.5 Gender Mainstreaming; I 2.2.1 Westeuropa; 370; 300; Jugendlicher; Migrant; Bildungsaspirationen; Bildungsaspirationen; Berufswunsch; Geschlechtsspezifische Faktoren; Geschlechtersegregation; Vereinigtes Königreich; Bundesrepublik Deutschland; Schweden; Niederlande